Key concepts in medication management in older persons for pharmacists practicing in non‐geriatric specialties. (5th October 2021) - Godbole, Gauri; Bolitho, Richard; Pont, Lisa
Abstract: Medication management for older persons can be complex. With over 50% of all hospital admissions being for people aged over 65 years, understanding age‐related functional, cognitive and social factor changes and their impact on medication use is critical for pharmacists working in most adult medicine areas. This paper provides an overview of critical elements of medication management for older persons for pharmacists. Key elements include age‐related changes impacting medication effectiveness and safety, frailty, geriatric syndromes, polypharmacy and deprescribing, minimising medication‐related harm at transitions of care, dose administration aids and other strategies to support individuals in medication management and multidisciplinary comprehensive geriatric assessment.